Effect of Sucrose Concentration on Microbiological, Physicochemical, Antioxidant Activity, and Organoleptic Characteristics of Salak Fruit Juice Beverage Fermented with Lactobacillus Plantarum InaCC B153 - Pandanwangi, Aisyah Amelia; Rosida, Rosida; Sudiana, I Made; Napitupulu, Toga Pangihitan; Kanti, Atit (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Salak is a tropical fruit that has great potential to be made into a healthy fermented beverage. The carbohydrate content and bioactive compounds such as phenolics in salak provide benefits as a source of antioxidants. The fermentation process will produce a probiotic drink that is good for digestive health. The fermentation process involves Lactobacillus plantarum bacteria as probiotic agents. This study aims to determine the effect of sucrose concentration on the characteristics of salak fruit juice probiotic drinks. This study used a completely randomised design (CRD) factorial pattern with sucrose concentration factor (3%, 6%, 9% b/v). The data obtained were analysed using ANOVA followed by DMRT further test at the 5% level. The results showed a significant interaction (p?0.05). Fermented salak fruit juice using 9% sucrose was the best treatment with characteristics of pH 3.80; total microbes 9.023 log CFU/ml; total acid 1,11%; total sugar 13,88%; viscosity 118,35 mPa.s; DPPH antioxidant activity 89.99%. The resulting organoleptic properties including colour, aroma, and taste, overall were 3.40 (moderately liked), 3.08 (moderately liked), 3.76 (moderately liked), and 3,48 (moderately liked).